Capnography - Gravenstein, J. S.; Jaffe, Michael B.; Graventsein, Nikolaus; Paulus, David A. (Cambridge University Press, 2011)
"In recent years capnography has gained a foothold in the medical field and is fast becoming a standard of care in anaesthesiology and critical care medicine. In addition, newer applications have emerged which have expanded the utility of capnographs in a number of medical disciplines. This new edition of the definitive text on capnography reviews every aspect of this valuable diagnostic technique. An introductory section summarises the basic physiology of carbon dioxide generation and transport in the body. A technical section describes how the instruments work, and a comprehensive clinical section reviews the use of capnography to diagnose a wide range of clinical disorders. Edited by the world experts in the technique, and with over 40 specialist contributors, Capnography, second edition, is the most comprehensive review available on the application of capnography in health care"--Provided by publisher.